2021
DOI: 10.18632/aging.203385
|View full text |Cite
|
Sign up to set email alerts
|

The life in a gradient: calcium, the lncRNA SPRR2C and mir542/mir196a meet in the epidermis to regulate the aging process

Abstract: The turnover of the epidermis beginning with the progenitor cells in the basal layer to the fully differentiated corneocytes is tightly regulated by calcium. Calcium more than anything else promotes the differentiation of keratinocytes which implies the need for a calcium gradient with low concentrations in the stratum basale and high concentrations in the stratum granulosum. One of the hallmarks of skin aging is a collapse of this gradient that has a direct impact on the epidermal fitness. The rise of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…Importantly, two independent studies both demonstrated that SPRR2C silencing suppressed cell proliferation, increased cell death, and inhibited the pro-inflammatory cytokine production presumably by influencing the PI3K/AKT/mTOR pathway. In addition, the level of endogenous SPRR2C transcript dynamically changes with age and SPRR2C appears to control keratinocyte differentiation [150]. These data collectively suggest that SPRR2C can be a critical hub gene in homeostatic regulation of keratinocytes and that SPRR2C may have potential roles in OLP progression.…”
Section: Sprr2c (Small Proline-rich Protein 2c)mentioning
confidence: 79%
“…Importantly, two independent studies both demonstrated that SPRR2C silencing suppressed cell proliferation, increased cell death, and inhibited the pro-inflammatory cytokine production presumably by influencing the PI3K/AKT/mTOR pathway. In addition, the level of endogenous SPRR2C transcript dynamically changes with age and SPRR2C appears to control keratinocyte differentiation [150]. These data collectively suggest that SPRR2C can be a critical hub gene in homeostatic regulation of keratinocytes and that SPRR2C may have potential roles in OLP progression.…”
Section: Sprr2c (Small Proline-rich Protein 2c)mentioning
confidence: 79%
“…Different calcium concentrations are required for various keratinocyte functions: low levels of calcium for proliferation and division of stem cells, and high levels of calcium to initiate the differentiation program and the formation of the cornified envelope [19,20]. Consequently, an epidermal calcium gradient is formed to meet these differential demands, with low levels of calcium in the stratum basale and stratum spinosum, rising and reaching its peak in the stratum granulosum, and declining again towards the outermost layers of the stratum corneum, where the keratinocytes reach their final differentiation status [21,22] (Figure 1). Calcium also regulates the expression of differentiation-specific proteins, such as loricrin, involucrin and filaggrin [23,24], and regulates keratinocyte migration and wound healing [25].…”
Section: Discussionmentioning
confidence: 99%
“…Skin diseases such as psoriasis [26] and atopic dermatitis [27] are characterized by a defective calcium gradient or malfunctioning calcium signalling. Indeed, also during the ageing process calcium signalling is impaired [28] and the calcium gradient collapses [22,29] which may in part underlie the ageing skin's reduced barrier function and epidermis thinning. Consequently, a potential therapeutic approach could be to replenish the calcium stores of not only aged, but also atopic and otherwise compromised skin, with topically applied calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Повышение концентрации кальция в базальном слое подавляет пролиферацию клеток, а снижение концентрации в зернистом слое изменяет состав ороговевшего слоя. Кератиноциты реагируют на вызванную кальцием блокировку деления клеток при старении усиленной экспрессией специфичных микроРНК, в том числе miR-552 [79]. При старении в тканях суставов и в сыворотке крови снижается экспрессия miR-708 [80].…”
Section: ассоциация со старением произошедших от ретроэлементов микро...unclassified